Student Athlete Rewarding System In Bandung City - Nuryadi Nuryadi; Bambang Abdul Jabar; Jajat Darajat Kusuma Negara; Agus Gumilar; Burhan Hambali (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
At the 2018 West Java Regional Sports Week, there were 1,822 athletes, mechanics, managers and officials involved. Researchers here review and conduct surveys and interviews with athletes and Koni West Java regarding the awards given to student athletes. Athlete career development is manifested in the form of educational scholarships for athletes within the Bandung City KONI from 2019 -2021, with the following percentages in 2019 of 33%, in 2020 33%, and in 2021 as much as 34% of the total scholarship budget that has been issued since 2019-2021 years. Scholarship recipients within the KONI Bandung City are tiered starting from the Middle School, Undergraduate, and Masters programs, through this student athlete program it is hoped that athletes will get decent jobs, so that after athletes retire from the world of sports they will get welfare in retirement.